What is precarious employment? A systematic review of definitions and operationalizations from quantitative and qualitative studies - Kreshpaj, Bertina; Orellana, Cecilia; Burström, Bo; Davis, Letitia; Hemmingsson, Tomas; Johansson, Gun; Kjellberg, Katarina; Jonsson, Johanna; Wegman, David H; Bodin, Theo (Scandinavian journal of work, environment & health, 2020)
Objectives The lack of a common definition for precarious employment (PE) severely hampers the comparison of studies within and between countries, consequently reducing the applicability of research findings. We carried out a systematic review to summarize how PE has been conceptualized and implemented in research and identify the construct's dimensions in order to facilitate guidance on its operationalization. Methods According to PRISMA guidelines, we searched Web of Science and Scopus for publications with variations of PE in the title or abstract. The search returned 1225 unique entries, which were screened for eligibility. Exclusion criteria were (i) language other than English, (ii) lack of a definition for PE, and (iii) non-original research. A total of 63 full-text articles were included and qualitative thematic-analysis was performed in order to identify dimensions of PE. Results We identified several theory-based definitions of PE developed by previous researchers. Most definitions and operationalizations were either an accommodation to available data or the direct result of qualitative studies identifying themes of PE. The thematic-analysis of the selected articles resulted in a multidimensional construct including the following three dimensions: employment insecurity, income inadequacy, and lack of rights and protection. Conclusions Despite a growing number of studies on PE, most fail to clearly define the concept, severely restricting the advancement of the research of PE as a social determinant of health. Our combined theoretical and empirical review suggests that a common multidimensional definition could be developed and deployed in different labor market contexts using a variety of methodological approaches.